A high selective ion‐imprinted polymer grafted on a novel nanoporous material for efficient gold extraction. Issue 11 (5th June 2013) - Moazzen, Elahe; Ebrahimzadeh, Homeira; Amini, Mostafa M.; Sadeghi, Omid
<x xml:space="preserve">Abstract</x> In this work, for the first time, an ion‐imprinted polymer was developed for selective extraction and determination of gold ions. To increase the sorbent efficiency, this polymer was coated on a novel nanoporous carbon‐based material, carbohydrate‐derived Max‐Planck Gesellschaft 1, which is also the first example of grafting imprinted polymer on nanoporous‐carbon material. These particles were applied successfully for preconcentration of ultratrace amount of gold ions, following determination by flame atomic absorption spectrometry. Some effective factors on the efficiency of gold ions extraction, such as concentration and volume of eluent, sample and eluent flow rates, and also effect of interfering ions especially palladium and platinum ions, were investigated. The LOD was determined to be 0.27 ng/mL. Furthermore, the precision of the method was calculated to be 2.14% under optimal conditions with recovery more than 97.3%. The technique was also used to determine the concentration of gold ions in mine stone samples with satisfactory results. The accuracy of this method was investigated by determination of gold ions concentrations in several reference materials with certified gold content.